Insects associated with Golden Berry in Cerro Punta, Chiriquí-Panamá (Aporte Santiaguino, 2019)
The purpose of this work was to identify the insects associated with aguaymanto in the location of CerroPunta. For this, three random samplings were carried out, choosing seven plants per sampling, fromwhich photographs were taken and specimens were collected, for later identification and diagnosis. Accordingto the results, respect to the phytophages, Antianthe expansa(Membracidae)was the most abundantspecies, followed by Oncopeltus sp. (Lygaeidae), Euschistus heros (Pentatomidae) and Epitrix sp.(Chrysomelidae). In case of predators, Zelus longipes, Z. renardii (Reduviidae) and Polybia sp. (Vespidae)were important; whereas in parasitoids, Enicospilus sp. (Ichneumonidae) and Pompilidae waspswere the most frequent. Apis mellifera (Apidae), was the main pollinator species, found in all plants andin all samples. In conclusion, there are at least 38 taxa associated with golden berry in Cerro Punta, fromwhich 45 % are phytophagous, 18 % predators, 24 % parasitoids, 8 % pollinators, 2 % detritivores and 3 %saprophytes. Although Antianthe expansa is an important pest of peppers and was the most abundantinsect observed during the study, the beneficial species found represent a potential to be explored, as anintegrated management strategy in the agroecosystem.
Keywords: host; beneficial insects; pest insects; highlands